Understanding Health Workers' Job Preferences to Improve Rural Retention in Timor-Leste : Findings from a Discrete Choice Experiment - Smitz, Marc-Francois (PLoS, 2019)
Timor-Leste built its health workforce up from extremely low levels after its war of independence, with the assistance of Cuban training, but faces challenges as the first cohorts of doctors will shortly be freed from their contracts with government. Retaining doctors, nurses and midwives in remote areas requires a good understanding of health worker preferences. The article reports on a discrete choice experiment (DCE) carried out amongst 441 health workers, including 173 doctors, 150 nurses and 118 midwives. Qualitative methods were conducted during the design phase. The attributes which emerged were wages, skills upgrading/specialisation, location, working conditions, transportation and housing.